2016
DOI: 10.1248/bpb.b15-00657
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Transnasal Delivery System for Recombinant Human Growth Hormone (rhGH): Effects of the Concentration and Molecular Weight of Poly-L-arginine on the Nasal Absorption of rhGH in Rats

Abstract: A novel system for delivering recombinant human growth hormone (rhGH) that is noninvasive and has a simple method of administration is strongly desired to improve the compliance of children. The aim of this study was to investigate the potential for the intranasal (i.n.) co-administration of rhGH with poly-L-arginine (PLA) as a novel delivery system by evaluating the effects of the concentration and molecular weight of PLA on the nasal absorption of rhGH. The influence of the formation of insoluble aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Furthermore, with the time of treatment, height and growth rate of children in the PGHD and CGHD groups significantly increased. 8 Previous studies have revealed that rhGH replacement therapy may affect the GHRH-GH-IGF-1 axis, liver function, the skeletal system, and glucose metabolism, and induce the development of insulin resistance, liver dysfunction, impaired glucose tolerance, femoral head spondylolisthesis, and scoliosis. 9 Therefore, in order to ensure the safety of the treatment, it is very necessary to conduct long-term follow-ups for GHD patients treated with rhGH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with the time of treatment, height and growth rate of children in the PGHD and CGHD groups significantly increased. 8 Previous studies have revealed that rhGH replacement therapy may affect the GHRH-GH-IGF-1 axis, liver function, the skeletal system, and glucose metabolism, and induce the development of insulin resistance, liver dysfunction, impaired glucose tolerance, femoral head spondylolisthesis, and scoliosis. 9 Therefore, in order to ensure the safety of the treatment, it is very necessary to conduct long-term follow-ups for GHD patients treated with rhGH.…”
Section: Discussionmentioning
confidence: 99%